IN VITRO STUDY OF FRACTAL ANALYSIS OF OSTEOTOMIES PERFORMED WITH DIFFERENT DESIGN IMPLANT DRILLS IN LOW DENSITY BONE BLOCKS - Ayşegül Öztürk; Volkan Arısan (Sabiad)
Objective: Alternative osteotomy techniques were introduced instead of the traditional drilling procedures of dental implant placement. One of these techniques is bone densification through a special design of drills. To study the effect of densification burs on low bone quality in comparison with conventional drilling procedures, the trabecular bone changes will be determined quantitively using fractal analysis (FA).Material and Methods: A control group (PKD) with the standard osteotomy burs and a test group (PV) with the osseodensification burs were used. In each group, 10 dental implants (4.2x10mm) were placed. A three dimensional (3D) image was obtained from the blocks on a Micro Computed Tomography (micro-CT) device. Fractal analysis was performed, and the results were analyzed by nonparametric tests (p<0.05).Results: According to the results, the FA value of apical and lateral areas from the PV group (1.292, 1.251 respectively) were significantly higher than the control group (p<0.01). When apical and lateral FA values of the PV group were compared, the apical values were found to be significantly higher than the lateral ones (p<0.01).Conclusion: In terms of fractal analysis, the bone densification effect of the burs in the PV group around the implants, compared to the PKD group, apical and lateral values, were found to be higher and have been found to provide better trabecular compression. FA may be useful for preoperative and non-invasive assessment of bone quality at implant sites.